Cold-induced changes in gene expression in brown adipose tissue, white adipose tissue and liver - Shore, Andrew M.; Karamitri, Angeliki; Kemp, Paul; Speakman, John R.; Graham, Neil S.; Lomax, Michael A. (Public Library of Science, 2013)
Cold exposure imposes a metabolic challenge to mammals that is met by a coordinated response in different tissues to prevent hypothermia. This study reports a transcriptomic analysis in brown adipose tissue (BAT), white adipose (WAT) and liver of mice in response to 24 h cold exposure at 8°C. Expression of 1895 genes were significantly (P<0.05) up- or down-regulated more than two fold by cold exposure in all tissues but only 5 of these genes were shared by all three tissues, and only 19, 14 and 134 genes were common between WAT and BAT, WAT and liver, and BAT and liver, respectively. We confirmed using qRT-PCR, the increased expression of a number of characteristic BAT genes during cold exposure. In both BAT and the liver, the most common direction of change in gene expression was suppression (496 genes in BAT and 590 genes in liver). Gene ontology analysis revealed for the first time significant (P<0.05) down regulation in response to cold, of genes involved in oxidoreductase activity, lipid metabolic processes and protease inhibitor activity, in both BAT and liver, but not WAT. The results reveal an unexpected importance of down regulation of cytochrome P450 gene expression and apolipoprotein, in both BAT and liver, but not WAT, in response to cold exposure. Pathway analysis suggests a model in which down regulation of the nuclear transcription factors HNF4α and PPARα in both BAT and liver may orchestrate the down regulation of genes involved in lipoprotein and steroid metabolism as well as Phase I enzymes belonging to the cytochrome P450 group in response to cold stress in mice. We propose that the response to cold stress involves decreased gene expression in a range of cellular processes in order to maximise pathways involved in heat production.